Determination of Fares for Online Transportation Applications with A Fare Bargaining System is Linked to Business Competition Law in Indonesia - Kalaj, Bernadetta Satyaayu Regitaningtyas; Gultom, Elisatris; Yuanitasari, Deviana (CV. Publikasi Indonesia, 2024)
This research aims to understand the practice of fare determination through a bidding system on online transportation applications based on Competition Law in Indonesia and to examine the supervision of fare determination actions through a bidding system on online transportation applications based on the applicable laws and regulations. This research employs a normative juridical analysis with a descriptive-analytical method by explaining the practice of fare determination using a bidding system and subsequently analyzing it using existing legal theories and norms. The results of this research indicate that the fare determination actions taken by online transportation business operators using a bidding system potentially violate the provisions of Article 20 of the Business Competition Law regarding the prohibition of predatory pricing and the Decree of the Minister of Transportation Number KP 667 in conjunction with the Decree of the Minister of Transportation Number KP 1001 concerning the Guidelines for Calculating Service Costs for Motorcycles Used with Applications, as well as the Minister of Transportation Regulation Number 12 of 2019 on the Protection of Safety for Motorcycle Users Used for Community Interests. Supervision of the actions of online transportation business operators in setting prices using a bidding system is conducted by two institutions, namely KPPU (Commission for the Supervision of Business Competition) and the Ministry of Transportation, both preventively and repressively.